Pengaruh Penambahan Mangan Terhadap Sifat Fisis Dan Mekanis Besi Cor Kelabu - Hengky Saputro, Irawan, Agus Yulianto, ST., MT (2017)
This research aims to know the influence of the addition of gray cast iron in manganese sand molds. This research uses a wooden cylinder pattern. Cast iron cylinder products serve as the ingredient testing. The test results obtained from the initial temperature meter when CE was cast in a mold 1356.80 C 1155.40 C liquid temperature, its shape is still liquid, the temperature of the solid 1113.60 C where a solid start but still iron is red until the temperature of the end 10600C. Results composition there are 6 elements effect on gray cast iron that is Fe = 0.0512, C = 0.0315, Si = 0.0175, Mn = 0.0037, Cr = 0.0018, Ni = 0.0004, the item contains more than 0.5%. There is A photo of micro graphite and cementit so that it can affect violence in every part and B there is a harder making perlit because mixing ferrite and cementit. Testing the hardness on the specimen without either Mn average reached 34.10 HRB, and specimens using Mn average 41.14 HRB. Tensile test results without the addition of Mn obtained the highest results maximum load of 26314.6 N, as well as Tensile Strength N/mm2 216.16, while specimens with the addition of the highest results obtainable Mn maximum load of 26812 N, whereas tensile strength N/mm2 216.75. Porosity that occurred on grey cast iron is caused by several factors, among others, casting and design patterns, print and design of sand mold and core, the composition of the metallic charge.